2007
DOI: 10.1007/s00226-007-0133-x
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical approach to wood fracture by three-dimensional mixed lattice-continuum model at fiber level

Abstract: To investigate the fracture behavior of wood, the porosity and heterogeneities of its microstructure should be taken into account. Considering these features of wood microstructure in a continuum-based model is still a difficult problem and the lattice model might be an alternative. In the developed mixed lattice-continuum model, the probable crack propagation volume was modeled by defining a three-dimensional lattice of different beam elements and the other regions were considered as continuum medium. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In addition, it was observed that fracture in spruce earlywood goes through the thin cell walls, as described by Gibson and Ashby (1997) for r/r s -0.2 with r/r s being the mean density related to the cell wall density, whereas interlamellar fracturing (in the middle lamella) was observed in latewood. Similar results are reported by Sedighi-Gilani et al (2007).…”
Section: Fracture At Cellular Levelsupporting
confidence: 92%
“…In addition, it was observed that fracture in spruce earlywood goes through the thin cell walls, as described by Gibson and Ashby (1997) for r/r s -0.2 with r/r s being the mean density related to the cell wall density, whereas interlamellar fracturing (in the middle lamella) was observed in latewood. Similar results are reported by Sedighi-Gilani et al (2007).…”
Section: Fracture At Cellular Levelsupporting
confidence: 92%
“…Introduced for wood by Landis et al (2002), this distinct view consists of modeling by a series of linear elements similar to the real wooden fibers. It was demonstrated that this approach provides satisfactory results at smaller scales, despite the higher complexity Brought to you by | University of Georgia Libraries Authenticated Download Date | 6/5/15 10:28 PM of construction and calibration (Davids et al 2003;Fournier 2005;Fournier et al 2007;Sedighi-Gilani and Navi 2007;Vasic and Stanzi-Tschegg 2007;Landis and Navi 2009;Nagy 2010;Nagy et al 2010). This approach facilitated the application of additional concepts in numerical wood models such as growth rings, mechanical variability, and heterogeneous failure patterns.…”
Section: Introductionmentioning
confidence: 92%
“…Sedighi-Gilani and Navi (2007) introduced longitudinally oriented beam elements in a 3D simulation of RL fracture. In both of these cases, the natural outcomes are damage patterns that mimic those observed in real specimens, as well as reasonable predictions of load-deformation measurements.…”
Section: Theoretical Backgroundmentioning
confidence: 99%